Summary Report: Agriculture-, Forestry-, and Fishing-Related Fatalities in Florida for 2020 - Serap Gorucu (EDIS)
This report summarizes Florida’s AgFF-related fatalities for 2020. This report helps to identify hazards and risks associated with agriculture, forestry, and fishing. Written by Serap Gorucu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, May 2021.